Chronic Kidney Disease as Risk Factor for Enlarged Perivascular Spaces in Patients With Stroke and Relation to Racial Group. Issue 11 (November 2020) - Penton, Ashley A.; Lau, Helena; Babikian, Viken L.; Shulman, Julie; Cervantes-Arslanian, Anna; Gangadhara, Suhas; Greer, David; Aparicio, Hugo J.; Romero, Jose R.
Abstract : Background and Purpose: Enlarged perivascular spaces (EPVS) are considered subclinical markers of small vessel disease, associated with increased risk of stroke and dementia. Increasing evidence links chronic kidney disease (CKD) to small vessel disease. We explored the relationship between CKD and EPVS burden and the influence of racial group in this relation. Methods: Consecutive patients with stroke who underwent brain magnetic resonance imaging were included (n=894). Racial group was categorized as White, Black, or other (other racial groups). CKD was defined by glomerular filtration rate <60 mL/minute per 1.73 m 2 for >3 months. EPVS were rated following a standardized method, dichotomized for analyses (mild [<20] versus severe [≥20]), and stratified by brain region (basal ganglia and centrum semiovale). Results: In multivariable-adjusted analysis, the association of CKD with severe EPVS varied across racial groups. Comparing patients with and without CKD within racial groups, we found that Whites with CKD had higher odds of severe centrum semiovale EPVS (odds ratio [OR], 2.41 [95% CI, 0.98–5.88]). Among patients with CKD, Black patients had higher odds of severe EPVS in the basal ganglia and centrum semiovale compared with Whites (OR, 1.93 [95% CI, 1.18–3.16] and OR, 1.90 [95% CI, 1.16–3.11], respectively) and other racial groups (OR, 2.03 [95% CI, 1.23–3.36] and OR, 2.02 [95% CI, 1.22–3.34], respectively). Conclusions: CKD was more prevalent in our sample of patients with stroke with severe EPVS in the centrum semiovale. The relation differed when stratified by racial group and brain topography. Further studies are needed to confirm that CKD may relate differently to subclinical measures of small vessel disease according to race. Abstract : Supplemental Digital Content is available in the text.